Electrical and optical properties of inorganic complexes C36H76N2O9ClNa and C14H12N2O4TeBr2 - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Aydogdu, A; Temel, H; Sekerci, M; Hosgoren, H (Editions Scientifiques Medicales Elsevier, 2001)
The electrical properties of some inorganic samples were studied as functions of temperature and the results were analyzed. These samples activation energies were calculated from the electrical conductivity measurements. Also, a detailed study of optical absorption is presented. The optical absorption spectra are measured in the UV+invisible wavelength range 200-1100 nm. The absorption coefficient and value optical energy gaps were determined from the absorption spectra. The complex C36H76N2O9ClNa is characterized by direct optical absorption with an optical edge at 4.49 eV. However, the complex C14H12N2O4TeBr2 is characterized by indirect optical absorption with an optical edge at 1.45 eV, and a nearby direct one at hv = 1.80 eV. (C) 2001 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: complex; transition metals; inorganic; semiconductor; activation energy